2009
DOI: 10.1104/pp.109.143875
|View full text |Cite
|
Sign up to set email alerts
|

SAUR39, a Small Auxin-Up RNA Gene, Acts as a Negative Regulator of Auxin Synthesis and Transport in Rice  

Abstract: The phytohormone auxin plays a critical role for plant growth by regulating the expression of a set of genes. One large auxinresponsive gene family of this type is the small auxin-up RNA (SAUR) genes, although their function is largely unknown. The expression of the rice (Oryza sativa) SAUR39 gene showed rapid induction by transient change in different environmental factors, including auxin, nitrogen, salinity, cytokinin, and anoxia. Transgenic rice plants overexpressing the SAUR39 gene resulted in lower shoot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
197
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 262 publications
(207 citation statements)
references
References 60 publications
7
197
3
Order By: Relevance
“…These proteins have been shown to bind with Ca 2+ /calmodulin proteins in maize (Yang and Poovaiah, 2000) and Arabidopsis (Reddy et al, 2002), to regulate auxin synthesis and transport in rice (Kant et al, 2009), or to control apical hook development in Arabidopsis (Park et al, 2007), but the roles of most of the SAUR proteins in plant growth and development have yet to be investigated. In this report, we demonstrate that SAUR36 plays a role in promoting leaf senescence in Arabidopsis, because leaf senescence is substantially delayed in the saur36 null mutant plants both phenotypically and physiologically (Fig.…”
Section: Suar36 Positively Regulates Leaf Senescence In Arabidopsismentioning
confidence: 99%
See 2 more Smart Citations
“…These proteins have been shown to bind with Ca 2+ /calmodulin proteins in maize (Yang and Poovaiah, 2000) and Arabidopsis (Reddy et al, 2002), to regulate auxin synthesis and transport in rice (Kant et al, 2009), or to control apical hook development in Arabidopsis (Park et al, 2007), but the roles of most of the SAUR proteins in plant growth and development have yet to be investigated. In this report, we demonstrate that SAUR36 plays a role in promoting leaf senescence in Arabidopsis, because leaf senescence is substantially delayed in the saur36 null mutant plants both phenotypically and physiologically (Fig.…”
Section: Suar36 Positively Regulates Leaf Senescence In Arabidopsismentioning
confidence: 99%
“…Studies of the maize (Zea mays) ZmSAUR2 protein revealed that SAUR expression may be regulated at the protein level (Knauss et al, 2003). Recent studies showed that OsSAUR39 acts as a negative regulator of auxin synthesis and transport; overexpression of this gene in rice (Oryza sativa) confers phenotypes including reductions in lateral root development, yield, and shoot and root lengths (Kant et al, 2009). The addition of an N-terminal GFP or epitope tag dramatically increases the stability of SAUR19 to SAUR24 proteins and their ability to function as positive effectors of cell expansion through the modulation of auxin transport (Spartz et al, 2012).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…72 Although the exact mechanism by which IAMT1 affects the expression of TCP genes is still obscure, it appears likely that perturbation of IAA homeostasis caused by altered expression of IAMT1 may be involved in this cross-communication. Since IAA3/SHORT HYPOCOTYL2 (SHY2) functions to suppress auxin response and a rice SMALL AUXIN UP RNA (SAUR) gene acts as a negative regulator of auxin synthesis and transport, 91,92 the direct activation of IAA3/SHY2 and a SAUR gene (At1g29460) by CIN-like TCPs indicates that these functionally redundant TCPs control lateral organ morphogenesis via exerting a negative effect on auxin response. 42,75 Despite the above-described roles of class II TCP genes in diverse developmental pathways, experimental evidence with respect to the developmental functions of class I TCP genes is still lacking.…”
Section: Developmental Functions Of Tcp Proteinsmentioning
confidence: 99%
“…The function of SAUR has been unknown, but recent studies have shown insights into the putative functions. Analyses of transgenic rice overexpressing the SAUR39 gene suggest that SAUR39 acts as a negative regulator for auxin synthesis and transport (Kant et al 2009). The Arabidopsis SAUR32 gene, which is a synonym of AAM1, is related to the apical hook development.…”
Section: ϩmentioning
confidence: 99%